Investigação de alterações estruturais possivelmente relacionadas à apatia na Doença de Parkinson - Thiago Macedo e Cordeiro (2023)
Introduction: Parkinson's disease (PD) is the second most common neurodegenerative disease and is characterized by motor and non-motor alterations like autonomic and neuropsychiatric symptoms. Among neuropsychiatric symptoms, apathy is present in up to 70% of patients and has a great impact over the development and treatment of PD. Neuroimaging studies highlight structural and functional alterations of the central nervous system (CNS) as important elements for the organic basis of PD and apathy. Objective: to investigate alterations in volume and cortical thickness of structures within the CNS of patients with PD and possible associations with apathy. Methods: Volumetric, cortical thickness, clinical, demographic and neuropsychiatric data from 30 PD patients were compared to 25 healthy controls. The groups were subdivided according to apathy scores. Possible correlations between apathy and structural alterations were also investigated. Structural measures of the central nervous system were obtained through magnetic resonance image processing with the FreeSurfer software for neuroimaging analysis. Results: when comparing structural measures between the PD group and controls, the PD group showed a reduction in the cortical thickness of the right temporal pole. The reduction remained statistically significant after controlling for confusion variables (p = 0.024). While controlling for confusion variables, the subgroup analysis showed a reduction in the central corpus callosum volume in the PD group with more apathy compared to the PD group with less apathy (p = 0.039). Correlation analysis showed an inverse correlation between the right temporal pole cortical thickness and apathy scores among patients with PD (r= -0.45; p = 0.027). The correlation remains significant after controlling for confusion variables like age, cognitive function and sex (p < 0.01). Conclusion: this was the first study that investigated associations between structural alterations and apathy in a Brazilian population with PD. Our findings corroborate the involvement of structural alterations of the CNS in the development of apathy. Our results also suggest that apathy in the context of PD may be linked to PD pathophysiological mechanisms that diverge from the classically associated mechanisms of apathy. Keywords: Parkinson's disease, apathy, neuropsychiatric symptoms, neuroimaging, right temporal pole, magnetic resonance imaging.